Evaluation of Cellulose in Diets with and without Added ZnO on Nursery Pig Performance - J. A. Chance; M. D. Tokach; H. I. Calderón; J. C. Woodworth; J. M. DeRouchey; R. D. Goodband (Kansas Agricultural Experiment Station Research Reports, 2020)
A total of 1,296 pigs (L337 × 1050; PIC, Hendersonville, TN; initially 10.6 lb) were used in a 42-d study to evaluate the addition of cellulose in diets with and without the inclusion of pharmacological levels of Zn on nursery pig growth performance. Pigs were weaned at approximately 20 d of age and randomly allotted to pens in a randomized complete block design by body weight (BW). Pens of pigs were allotted to 1 of 4 dietary treatments with 27 pigs per pen and 12 replications per treatment. Dietary treatments were arranged in a 2 × 2 factorial with main effects of cellulose (0 vs. 1%; J. Rettenmaier USA LP, Schoolcraft, MI) and Zn (200 ppm vs. 3,000 ppm in phase 1 diets and 110 ppm vs. 2,000 ppm in phase 2 diets with added zinc provided by zinc oxide). Treatment diets were formulated in two dietary phases which were fed from approximately d 0 to 7 and 7 to 21 with a common phase 3 diet fed from d 21 to 42 post-weaning. Pig weights and feed disappearance were collected weekly to determine average daily gain (ADG), average daily feed intake (ADFI), and feed efficiency (F/G). On day 16 or 17, fecal samples were collected from 3 pigs per pen to determine fecal DM, and all pens were visually evaluated for fecal consistency. There were no Zn × cellulose interactions observed. For the experimental period (d 0 to 21), pigs fed diets containing added Zn had increased (P<0.001) ADG, ADFI, and BW and improved (P<0.001) F/G while those that were fed cellulose had decreased (P= 0.011) ADG. For fecal dry matter, there was no evidence for difference (P>0.10) between any of the four dietary treatments but those fed added ZnO had visually firmer feces (P<0.001). When pigs were fed a common diet (d 21 to 42), pigs previously fed diets containing added ZnO had increased (P<0.001) ADG and ADFI. For the overall period (d 0 to 42), pigs that had been fed added Zn had increased (P<0.001) ADG, ADFI, and BW and improved (P<0.001) F/G, while those that had been fed cellulose had decreased (P= 0.023) ADG. In conclusion, there were no interactive effects between added cellulose and Zn. The addition of cellulose reduced ADG, but did not affect F/G, while the inclusion of pharmacological levels of Zn improved all growth criteria.
Keywords: cellulose; fecal dry matter; growth; nursery pigs; zinc